2021
DOI: 10.1007/s00068-021-01720-1
|View full text |Cite
|
Sign up to set email alerts
|

Measuring functional outcomes in major trauma: can we do better?

Abstract: There is relatively limited large-scale, long term unified evidence to describe how quality of life (QoL) and functional outcomes are affected after polytrauma. The aim of this study is to review validated measures available to assess QoL and functional outcomes and make recommendations on how best to assess patents after major trauma.Methods: PubMed and EMBASE databases were interrogated to identify suitable patient reported outcome measures (PROMs) for use in major trauma, and current practice in their use g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 84 publications
(180 reference statements)
0
3
0
Order By: Relevance
“…We would like to congratulate the authors on the publication of the literature review showing the heterogeneity of patient reported outcome measures (PROMs) used in trauma patients [ 1 ].…”
mentioning
confidence: 99%
“…We would like to congratulate the authors on the publication of the literature review showing the heterogeneity of patient reported outcome measures (PROMs) used in trauma patients [ 1 ].…”
mentioning
confidence: 99%
“…This reinforces the need for urgent, robust, evidenced-based, randomized clinical trials to evaluate the benefits, risks, and indications of permissive weight-bearing after fixation of acetabular fractures. Finally, the use of the current existing patient-reported outcome measurements (PROMs) appears to be insufficient to truly assess the role of the “ability to walk” in terms of pain management, return to a pre-injury functional level, and quality of life, all of which are important components for better understanding the relationship between patient satisfaction and patient trust in the attending physician and the treatment carried out [ 58 , 59 , 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…PROMs and PREMs provide a surrogate marker of effectiveness of treatment and burden of a disease and have emerged as optimal assessment tools over the last decade ( 106 , 107 , 108 ). In the literature, there are scarce reports of the late outcome of trauma patients which document the severe impact of certain injuries long term and the need for longitudinal monitoring of this population ( 109 , 110 ).…”
Section: Key Elements Of the Aftercare/rehabilitation Phasementioning
confidence: 99%